Systematic theology ; v. 4 - Geisler, Norman L. 1932- (Minneapolis, MN Bethany House, 2008)
Contents : v. 4 : Church; Last things. Includes bibliographical references and indexes.
Keywords: Theology, systematic; Bible -- introductions